(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Jhpiego provides contextual evidence-based real-life solutions that contribute to saving lives, improving health, and transforming futures for women, children, and their families living in more than 42 countries. Over its 50 years of existence and a geographic footprint of more than 150 countries, this JHU-affiliated NGO has contributed to the introduction and scale-up of multiple life-saving innovations, has been a dot connector, a trusted partner to many governments and professional and local organizations, and an innovator. In Kenya, Jhpiego has worked for more than 45 years, partnering with KOGS in multiple initiatives, and has contributed to the development and review of multiple evidence-based policies and recommendations at the global, regional, and national levels. Evidence-based practice plays a critical role in improving the quality of reproductive health care. While global recommendations are important, they require adaptation to local contexts for full implementation to be practical. Introduction of heat-stable carbetocin and the scale-up of the E-MOTIVE bundle to manage PPH, respectful care, and mental health in RH, introduction and scale-up of post-pregnancy FP, introduction and scale-up of primary and secondary cervical prevention interventions, the use of blended learning that uses multiple delivery channels, including the use of AI-powered training tools that respond to the needs of health providers, and supporting the quality of services through approved pharmacies, including e-pharmacy.